(6,7-Dimethoxy-4-methylisoquinolinyl)-(4 `-methoxyphenyl)-methanone, a New Benzylisoquinoline Alkaloid from Beilschmiedia brevipes - Pudjiastuti, P.; Mukhtar, M.R.; Hadi, A.H.A.; Saidi, N.; Morita, H.; Litaudon, M.; Awang, K. (2010)
The leaves of Beilschmiedia brevipes provided a new benzylisoquinoline alkaloid: (6,7-dimethoxy-4-methylisoquinolinyl)-(4'-methoxyphenyl)-methanone (1) and O,O-dimethylannocherin A (2), a new natural compound which has been synthesized before. Complete H-1- and C-13-NMR data of both compounds were reported. The structures were established through various spectroscopic methods notably 1D- and 2D-NMR, UV, IR and HRESIMS.